Bursera graveolens essential oil: Physiochemical characterization and antimicrobial activity in pathogenic microorganisms found in Kajikia audax - Noel-Martinez, Kevin Carlos (2021)
The authors thank to Universidad Nacional de Tumbes, Universidad Nacional de Ingenieria and Fondo Nacional de Desarrollo Cientifico, Tecnologico y de Innovacion Tecnologica (Contrato No 02-2018-FONDECYT-BM-IADT-MU).